Pengaruh Rasio VCO Wortel (Daucus carota L.) Dan Lemak Kakao (Theobroma cacao L.) Serta Lama Pengadukan Terhadap Karakteristik Sediaan Krim - Puspita, Adhe Sri Nanda; Wrasiati, Luh Putu; Dewi Anggreni, Anak Agung Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 11 No 1 (2023): MaretDO - 10.24843/JRMA.2023.v11.i01.p11, 2023)
ABSTRACT: Carrot extract, cocoa butter and VCO conduct many benefits for the body as we know they are rich in antioxidants.  This research aims to determine the effect of the VCO wortel and cocoa butter and stirring time on the characteristics of the cream preparation, determine the ratio of VCO wortel and cocoa butter as well as the appropriate stirring time to produce the best cream preparation.  This study used a factorial randomized block design with two factors.  The main factor is the concentration of the addition of VCO wortel which consists of 3 levels, namely 1:5, 1:7, 1:9.  The second factor is the stirring time which consists of 3 levels of 10 minutes, 15 minutes, 20 minutes.  This research was conducted in 2 groups with 9 combinations so that 18 experimental units were obtained. The data obtained were then analyzed by analysis of variance (ANOVA) and continued with Tukey's further test using Minitab 17 software. The results showed that the effect of  VCO wortel, cocoa butter and stirring time and their interactions had an effect on viscosity, spreadability, separation ratio, adhesion, pH, L* color, b* color, homogeneity, IC50 antioxidant activity but color a* interaction does not affect the characteristics of the cream preparation. The ratio of VCO wortel and cocoa butter and stirring time to the characteristics of the cream preparation with a ratio of 1:9 at a stirring time of 20 minutes is the best cream preparation, namely viscosity 40,050±141, spreadability 4.07±0.04, adhesion 7,25 ±0.03, pH 6,25±0.01, L* color 68,43±0,02, b* color 29,54±0,01, antioxidant activity IC50 875.73±1. KATA KUNCI: carrot VCO, cocoa butter, stirring time, characteristics cream.